ಮೌಲ್ಯನಿರ್ಧಾರಣ ಪಾರಿಭಾಷಿಕ ಪದಕೋಶ - (:unkn) unknown (My University, 2017)
The 'Glossary of Evaluation Terms in Kannada' consists of about 1000 key terms in two lists, viz., 'Kannada to English' and 'English and Kannada'. The terms are from the disciplines of education, linguistics, literature, personality, psychology, statistics, etc. that together represent the concepts used in the area of educational testing and evaluation. The present work is a milestone in the march toward achieving the goal and vision NTS-India.
Glossary of Evaluation Terms Kannada-English-Kannada
Keywords: Kannada; English